2021
DOI: 10.1016/j.lungcan.2021.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated glutamate to pro-collagen conversion is associated with adverse outcome in lung cancer and may be targeted by renin-angiotensin-aldosterone system (RAS) inhibition

Abstract: Background:The tumor-microenvironment (TME) represents an attractive therapeutic target in NSCLC and plays an important role for efficacy of cancer therapeutics. We hypothesized that upregulation of collagen synthesis might be associated with adverse outcome in NSCLC. Literature evidence suggests that renin-angiotensin system inhibitors (RASi) decrease collagen deposition. Therefore, we aimed to explore the prognostic role of RASi intake and their influence on the TME in NSCLC. Methods: Four publicly available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Currently, this is the only report of mortalin directly binding to these specific proteins. Overexpression of ALDH18A1 in cancer supports accelerated metabolism, angiogenesis, metastases and chemotherapy resistance ( Tang et al, 2018 ; Ding et al, 2020 ; Guo et al, 2020 ; Rohlenova et al, 2020 ; Shenoy et al, 2020 ; Kocher et al, 2021 ). Complexes of CTPS1 and inosine monophosphate dehydrogenase type 2 (IMPDH2), called cytoophidia or rods and rings, regulate key steps in CTP and GTP biosynthesis.…”
Section: Sheta2 Disruption Of Mortalin Support Of Mitochondria and Me...mentioning
confidence: 99%
“…Currently, this is the only report of mortalin directly binding to these specific proteins. Overexpression of ALDH18A1 in cancer supports accelerated metabolism, angiogenesis, metastases and chemotherapy resistance ( Tang et al, 2018 ; Ding et al, 2020 ; Guo et al, 2020 ; Rohlenova et al, 2020 ; Shenoy et al, 2020 ; Kocher et al, 2021 ). Complexes of CTPS1 and inosine monophosphate dehydrogenase type 2 (IMPDH2), called cytoophidia or rods and rings, regulate key steps in CTP and GTP biosynthesis.…”
Section: Sheta2 Disruption Of Mortalin Support Of Mitochondria and Me...mentioning
confidence: 99%
“…The close implication of the collagen family in tumorigenesis has been well documented. 19 , 20 , 21 , 22 , 23 , 24 For example, collagen prolyl 3-hydroxylation (P3H) was shown to have low expression in lung cancer, whereas its overexpression suppressed cancer cell growth, migration, and invasion, and it had pro-apoptotic roles in lung cancer. 25 As expected, COL3A1 has vital roles in carcinogenesis, where it serves as an oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study on the identification of candidate genes affecting mastitis in cows showed that ALDH18A1 was among DEGs in mammary tissue after intramammary infection with E. coli or Streptococcus uberis (Chen et al 2015 ). ALDH18A1 is one of the genes in the collagen synthesis pathway (Kocher et al 2021 ). Therefore, ALDH18A1 can be considered an important gene in mastitis induced by E. coli .…”
Section: Discussionmentioning
confidence: 99%